Genetic and molecular insights into genotype-phenotype relationships in osteopathia striata with cranial sclerosis (OSCS) through the analysis of novel mouse Wtx mutant alleles - Comai, Glenda; Boutet, Agnès; Tanneberger, Kristina; Massa, Filippo; Rocha, Ana Sofia; Charlet, Aurelie; Panzolini, Clara; Jian Motamedi, Fariba; Brommage, Robert; Hans, Wolfgang; Funck-Brentano, Thomas; Hrabe de Angelis, Martin; et al. (Journal of Bone and Mineral Research, 2018)
The X-linked WTX/AMER1 protein forms an important component of the ?-catenin destruction complex that can both enhance and suppress canonical ?-catenin signalling. Somatic mutations in WTX/AMER1 have been found in a proportion of the pediatric kidney cancer Wilms' tumour. By contrast, germline mutations cause the severe sclerosing bone dysplasia osteopathia striata congenita with cranial sclerosis (OSCS), a condition usually associated with fetal or perinatal lethality in male patients. Here we addressed the developmental and molecular function of WTX by generating two novel mouse alleles. We show that in addition to the previously reported skeletal abnormalities, loss of Wtx causes severe midline fusion defects including cleft palate and ectopic synostosis at the base of the skull. By contrast, deletion of the C-terminal part of the protein results in only mild developmental abnormalities permitting survival beyond birth. Adult analysis however revealed skeletal defects including changed skull morphology and an increased whole body bone density, resembling a subgroup of male patients carrying a milder, survivable phenotype. Molecular analysis in vitro demonstrated that while ?-catenin fails to co-immunoprecipitate with the truncated protein, partial recruitment appears to be achieved in an indirect manner using AXIN/AXIN2 as a molecular bridge. Taken together our analysis provides a novel model for WTX-caused bone diseases and explains on the molecular level how truncation mutations in this gene may retain some of WTX-protein functions. This article is protected by copyright. All rights reserved.
EVALuna2:10311